Model Experimental Study of Carbon Fiber Heating Wire for Deicing and Snow Melting on a Bridge Deck - Yan Tan; Yuntao Zhu; Henglin Xiao (Advances in Civil Engineering)
In order to use the carbon fiber heating wire more efficiently and safely, the influence of the built-in carbon fiber heating wires (CFHWs) on the temperature changes of the bridge deck is studied in this paper. The model experiments of the temperature rise and ice melting are carried out in a room with low temperature cold storage environment, and the temperature variation of the specimens under different ambient temperatures, namely, −2, −4, and −8°C, was measured. The results show that, in the temperature rise experiment, the temperature change rate of the measuring points of the surface layer in the central part above CFHW is the most obvious, with the temperature change rate of 2.123°C/h; owing to the limited radiation range of CFHW, the temperature change rate of the measuring points between the CFHW and the CFHW of the surface layer decreases significantly, with a value of 0.703°C/h, and the temperature of the measuring points of the heating layer where CFHW is located shows a nearly linear increase, with a temperature change rate of 1.313°C/h. The temperature of the bridge deck is basically above 0°C as most of the heat generated by CFHW is transferred to the bridge deck after heating, which can effectively prevent the bridge deck from freezing. In the ice melting experiment, the temperature change rate of the measuring points of the surface layer in the central part above the CFHW is 1.406°C/h, and the maximum temperature change rate of the measuring points between the CFHW and CFHW of the surface layer is 0.408°C/h. The overall ice melting condition on the specimen surface is appreciable. When the heating power is set to 190 W/m2, the influence of the ambient temperature on the measuring points of the surface layer is negligible, but the influence of the ice melting rate at different positions from the heating wire is obvious. Therefore, it can be seen that optimizing the layout of the CFHW can effectively improve the whole uniformity and efficiency of ice melting of the bridge deck. The results from relevant research can provide a reference for the design and operation of deicing and snow melting applications on a bridge deck.